The Circadian Clock Gene, TaPRR1, Is Associated With Yield-Related Traits in Wheat (Triticum aestivum L.) - Sun, Han; Zhang, Wenping; Wu, Yongzhen; Gao, Lifeng; Cui, Fa; Zhao, Chunhua; Guo, Zhiai; Jia, Jizeng (Frontiers in Plant Science, 2020)
Timing of flowering is crucial for the transformation from vegetative to reproductive growth in the important food crop, wheat (Triticum aestivum L.). The circadian clock is a central part of photoperiod regulation, with Pseudo-Response Regulators (PRRs) representing key components of circadian networks. However, little is known about the effects of PRR family members on yield-related traits in crop plants. In this study, we identified polymorphisms and haplotypes of TaPRR1, demonstrating that natural variations in TaPRR1 are associated with significant differences in yield-related traits including heading date, plant height and thousand grain weight. TaPRR1-6A-Hapla showed an earlier heading date, advanced by 0.9% to 1.7%. TaPRR1-6B-Hapla and TaPRR1-6D-Hapla displayed reduced plant height and increased thousand grain weight of up to 13.3% to 26.4% and 6.3% to 17.3%, respectively. Subcellular localization and transcriptional activity analysis showed that TaPRR1 is a nuclear localization protein with transcriptional activity controlled by an IR domain. The expression profiles of TaPRR1 genes over a 48-h period were characterized by circadian rhythms, which had two peaks under both short- and long- day conditions. In addition, geographical distribution analysis indicated higher distribution frequencies of TaPRR1-6A-Hapla, TaPRR1-6B-Haplb, and TaPRR1-6D-Haplb in different agro-ecological production zones. Furthermore, analysis of molecular variance of the distribution frequency of TaPRR1 haplotypes suggested significant differences in haplotype distribution frequency between landraces and modern cultivars. Our study provides a basis for in-depth understanding of TaPRR1 function on yield-related traits in wheat, as well as establishing theoretical guidance for wheat molecular marker-assisted breeding.